1989
DOI: 10.1128/iai.57.3.957-962.1989
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic analysis of Campylobacter species and an intracellular Campylobacter-like organism associated with porcine proliferative enteropathies

Abstract: Whole-cell and outer membrane preparations of Campylobacter mucosalis, C. hyointestinalis, C. jejuni, and C. coli isolated from porcine intestines were compared with preparations of intracellular Campylobacter-like organisms extracted directly from the lesions of pigs with proliferative enteropathy. By gradient polyacrylamide gel electrophoresis, outer membrane and total protein profiles of C. mucosalis, C. hyointestinalis, C. jejuni, and C. coli were significantly different from each other and from those of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 24 publications
(32 reference statements)
1
18
0
2
Order By: Relevance
“…As reported by other investigators (9,14,16,20), flagella were not observed in any of the light or electron microscopic preparations. The organism exhibited a dramatic motility within the cytoplasm of infected Intestine 407 cells examined by phase microscopy, indicating the presence of some mechanism for motility.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As reported by other investigators (9,14,16,20), flagella were not observed in any of the light or electron microscopic preparations. The organism exhibited a dramatic motility within the cytoplasm of infected Intestine 407 cells examined by phase microscopy, indicating the presence of some mechanism for motility.…”
Section: Discussionsupporting
confidence: 80%
“…Porcine proliferative enteropathy is a disease of pigs with similar lesions and possibly the same etiology as hamster proliferative ileitis (15). Antigenic (14) and DNA (16) analysis of a preparation of intracellular organisms recovered from pigs with porcine proliferative enteropathy has suggested that the intracellular organism is unrelated to the presently described Campylobacter spp. and may not be a member of the genus Campylobacter.…”
mentioning
confidence: 99%
“…Although this species was initially isolated from pigs with prolifer-ative enteritis, it is now known that that disease in pigs is caused by Lawsonia intracellularis. 29,36 Campylobacter species have also been identified by PCR from DNA extracted from bile and biliary epithelium in humans with hepatolithiasis. 23 In addition, mice experimentally infected with Campylobacter jejuni develop severe hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, use of these bacteria as oral inocula has never reproduced the specific disease (2,14). The conclusion that the intracellular bacteria in the lesions were likely to belong to a separate group of Campylobacter-like organisms requiring cells for growth was supported by immunologic and DNA studies on intracellular bacteria purified from the lesions (6,15). This led to our recent development of a successful cell culture system for the intracellular bacteria, using the rat enterocytes IEC-18 (10).…”
mentioning
confidence: 99%